Impact of Endemic Infections on HIV Susceptibility in Sub-Saharan Africa - Sergey Yegorov; Vineet Joag; Ronald M. Galiwango; Sara V. Good; Brenda Okech; Rupert Kaul (Tropical Diseases, Travel Medicine and Vaccines, 2019)
Abstract Human immunodeficiency virus (HIV) remains a leading cause of global morbidity with the highest burden in Sub-Saharan Africa (SSA). For reasons that are incompletely understood, the likelihood of HIV transmission is several fold higher in SSA than in higher income countries, and most of these infections are acquired by young women. Residents of SSA are also exposed to a variety of endemic infections, such as malaria and various helminthiases that could influence mucosal and systemic immunology. Since these immune parameters are important determinants of HIV acquisition and progression, this review explores the possible effects of endemic infections on HIV susceptibility and summarizes current knowledge of the epidemiology and underlying immunological mechanisms by which endemic infections could impact HIV acquisition. A better understanding of the interaction between endemic infections and HIV may enhance HIV prevention programs in SSA.